PENERAPAN LAYANAN KONSELING REBT UNTUK MENGURANGI KEBIASAAN MENONTON FILM PORNO DI INTERNET (Studi Kasus di Kelas VIII SMP Negeri 13 Pontianak) - Noventy, Ading Ero; Asrori, Muhammad; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research aims to find out and analyze in depth about students who have the habitual behavior of watching porn on the internet at SMP Negeri 13 Pontianak using two case subjects in class VIII. This research method uses descriptive methods with a qualitative approach in the form of case studies. The counseling model used in treatment to handle and alleviate these problems is Rational Emotive Behavior Therapy (REBT) using didactic and directive techniques and with data collection techniques including observation, interviews and documentation. The factors that cause the case subject to have the habitual behavior of watching porn on the internet which has many negative impacts are due to two factors, namely internal and external factors. The results showed that there were positive changes that appeared in case subject I and case subject II after the treatment was given four times. Changes that appear in the case subject include the case subject being able to reduce the habitual behavior of watching pornographic films on the internet, the case subject has also committed to doing positive activities both at school and at home.